2013
DOI: 10.1103/physrevb.88.094425
|View full text |Cite
|
Sign up to set email alerts
|

Coherent magnon and acoustic phonon dynamics in tetragonal and rare-earth-doped BiFeO3multiferroic thin films

Abstract: Coherent magnons and acoustic phonons were impulsively excited and probed in thin films of the room temperature multiferroic Bi 1−x−y Dy x La y FeO 3 using femtosecond laser pulses. The elastic moduli of rhombohedral, tetragonal, and rare-earth doped BiFeO 3 were determined from acoustic-mode frequencies in conjunction with spectroscopic ellipsometry. A weak ferromagnetic order, induced alternately by magnetization in the growth direction or by tetragonality, created a magnon oscillation at 75 GHz, indicative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
23
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
4
23
2
Order By: Relevance
“…However, the high frequency (75 GHz) feature cannot result from the acoustic phonon mechanism, as the oscillation is present at all time delays. In a previous study of magnons in BiFeO 3 thin films a mode at a comparable frequency was found to disappear above the Néel temperature37. Both the PTFO films reported here and the BiFeO 3 films previously studied37 had LaAlO 3 substrates, and therefore have comparable in-plane lattice constants and Fe-Fe distances (assuming that there are regions of the PTFO samples with Fe ions in adjacent cells).…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…However, the high frequency (75 GHz) feature cannot result from the acoustic phonon mechanism, as the oscillation is present at all time delays. In a previous study of magnons in BiFeO 3 thin films a mode at a comparable frequency was found to disappear above the Néel temperature37. Both the PTFO films reported here and the BiFeO 3 films previously studied37 had LaAlO 3 substrates, and therefore have comparable in-plane lattice constants and Fe-Fe distances (assuming that there are regions of the PTFO samples with Fe ions in adjacent cells).…”
Section: Resultssupporting
confidence: 60%
“…Time-resolved reflectivity thus permits electronic generation and relaxation processes to be examined. Further, coherent oscillations in Δ R can result from magnons in multiferroics3637. The observed transients for the PTFO films (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…From these we obtain C 11 = 58(6) GPa, C 44 = 42(4) GPa, C 12 = 17(2) GPa, and the bulk modulus B = 1 3 (C 11 + 2C 12 ) = 31(3) GPa. We note that the room temperature values of the longitudinal elastic constant C 11 derived from previous experimental 19,23,24 and theoretical work 25,26 on BiFeO 3 are highly inconsistent. The value of C 11 ranges from ≈ 60 GPa (our neutron measurements), to ≈ 125 GPa (ultrasonic measurements), to ≈ 207 GPa (x-ray inelastic measurements).…”
Section: Resultsmentioning
confidence: 64%
“…17 The rapid photo-induced mechanical stress results in the excitation of coherent acoustic phonons and magnons. 18,19 The dynamics of photo-induced strain was directly and quantitatively measured in a synchrotron-based ultrafast X-ray diffraction. 20 One of the most straightforward implementations of ultrafast spectroscopy is the hot electron transient relaxation following the photo-excitation.…”
mentioning
confidence: 99%